EPISTEMOLOGI FAZLUR RAHMAN DALAM MEMAHAMI ALQURAN DAN HADIS - M Samsul Ma'arif (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2016)
Abstract: Epistemology of Fazlur Rahman in Understanding the Qur’an and Hadith. This article examines the epistemology of Fazlur Rahman in understanding the Qur’an and the hadith, and was his thought of the qur’an and hadith relevance to the modern era. This research is a library research, using a hermeneutic approach or historical-critical approach. The collected datas are analyzed in descriptive-analytic. The results showed; Firstly, epistemology of Fazlur Rahman in understanding the Qur’an and the hadith is epistemology of Burhani, this epistemology is based on observation and experimentation which is systematized with the operationalization of the methods of historical criticism, sistematic interpretation and refined by the method of double movement. While the arguments reasoning used in understanding the Qur’an and the hadith is a demonstrative argument, verification and exploratory with a historical approach, normative and philosophical. Secondly, epistemology of Fazlur Rahman has significant relevance to the development of qur’anic and hadith thought in the modern era, mainly in the aspect of development and methodology system. However, with regard to the evolution of the sunna and the hadith, although it has defended his entity from the orientalist, Fazlur Rahman has a conception of liberal and dangerous, because he doubted the validity of most of the traditions of the technical contained in the books of hadith, he thought that the itsnad does not ensure the validity of the hadith, because itsnads itself is emerging at the end of the first century AH.